Appropriate technology dissemination to increase cassava chips production capacity - Rosyidi, Muhammad Imron; Wicaksono, Bagas Rasyid; Ramadhani, Mughni Rizqi; Pratama, Gilang Adhi Priambudi; Dinda M, Zahra Yasmin; Rozaqna M, Muhammad (Community Empowerment, 2021)
Small and Medium Enterprises of Cassava Chips are home-based businesses that many families have worked on in Kedungan, Sambeng Village, Borobudur District, Magelang Regency. In this home-based business, they generally face problems, namely efficiency and relatively low productivity. This problem was caused by the part of the cassava chips molding process which still uses simple tools. This problem can be solved by making a cassava chip molding machine capable of producing cassava chips with a printing speed of 167 chips / 5 minutes and a thickness of 0.8 mm chips. The machine has three main parts, namely the driving part by utilizing a pedal to rotate the roller-shaped blade, the roller-shaped blade which functions most importantly for pressing cassava dough which has been milled into a mold in the form of cassava chips, and fiber which functions to put the pressed casava chips mold.